APPLICATION OF THE THIRD PRECEPT VALUES OF PANCASILA IN FORMING STUDENT DISCIPLINE AND LOVE OF COUNTRY THROUGH PASKIBRA EXTRACURRICULAR ACTIVITIES - Khoirunisa Hafida; Jawatir Pardosi; Suryaningsih; Novita Majid (SOSIOEDUKASI, 2025)
This study aims to analyze the application of Pancasila values, particularly the third principle of “The Unity of Indonesia”, in the formation of discipline and patriotism of students through Paskibra extracurricular activities at SMA Negeri 7 Balikpapan. The background of this research is based on the urgency of instilling character education as an effort to strengthen the spirit of nationalism in the midst of globalization that has the potential to erode the values of nationalism of the younger generation. This research uses qualitative approach with descriptive research type. The data collection technique is conducted through observation, interview, and documentation to the coach and active members of Paskibra in SMA Negeri 7 Balikpapan. The result of the research shows that Paskibra activities have a strategic role in instilling the values of the third principle of Pancasila through the formation of discipline, nationalism, cooperation, and shared responsibility. These values are reflected through the concept of “Jiwa Korsa”, respect for state symbols and habits embedded from various routine activities. The research contributes to the strengthening of civic education and can be used as a reference in character building in the school environment.